Identifikasi Potensi Air Tanah Menggunakan Metode Geolistrik Resistivitas Konfigurasi Schlumberger di Kelurahan Bapangsari Kecamatan Bagelen Kabupaten Purworejo - Taufik Nur Fitrianto; Supriyadi Supriyadi; Ulil Albab Taufiq; Teguh Maulana Mukromin; Anggit Pranatya Wardana (Lambung Mangkurat University Press, 2018)
This research aimed to determine location and distribution of groundwater in Bapangsari, Bagelen, Purworejo. This research used Vertical Electrical Sounding (VES) method with Schlumberger configuration. Research data were taken by using resistivity meter IPMGEO. This research did on 2 locations with length of line is 180 m. The data were processed using software Microsoft Excel and IP2WIN. Based on result of the research. On the first location, groundwater is at 32,2 m depth with 3,3 m thick. On the first location, groundwater is at 34,6 m depth with 9,58 m thick. Groundwater on the first location is shallower than second location. However, on the first location have over burden. The over burden has big enough resistivity value (higher than 100 ohm m). This value has been identifying of a solid layer. The layer is andesitic breccia. While on second location, the over burden has small enough resistivity value (50 ohm m). This value has been identifying of a sedimentary layer. The layer is weathered breccia and gravel.